Evaluation of acrosome integrity in epidydimal alpaca sperm by flow cytometry - Ugarelli, Alejandra (2017)
The aim of this study was to determine the percentage of epidydimal sperm acrosome integrity using alpaca Arachis hypogaea (PNA) and Pisum sativum (PSA), combined with fluorescein isothiocyanate (FITC). Testicles (n=45) were obtained at Ninacaca municipal slaughterhouse (Pasco, Peru). Only 29 samples with motility higher than 30% and concentration higher than 50x106 sperm/ml were used. Sperm from cauda epididymis were recovered with 1 ml of Tris base solution, and then, washed by centrifugation at 600 g for 8 min and pellets were re-suspended in 300 μl of PBS. Each sample was divided into two aliquots and incubated for 8 min at 38 °C with FITC-PNA (0.5 μg/ml) or FITC-PSA (2.5 μg/ mL) together with propidium iodide (PI, 0.5 μg/ml) as a viability marker. Samples were evaluated by flow cytometry using a laser excitation 488 nm and emission detector channels 505-560 nm fluorescence (channel 02 for FITC) and 642-740 nm (Channel 05 for PI). Sperm emitting green fluorescence on Channel 02 were considered with acrosome damage while sperm emitting red fluorescence on Channel 05 were considered dead. The results showed 59.17 ± 4.84 and 61.13 ± 4.35% of live sperm with acrosome integrity when using FITC-PNA and FITC-PSA respectively. These results are an indicator of epididymal sperm acrosome integrity in alpaca and can provide the basis for studying sperm physiology in this specie.